Hebrew Translations of Palestinian Literature — from Total Denial to Partial Recognition - Amit-Kochavi, Hannah (TTR)

(untitled) (Association canadienne de traductologie, 2000)
AbstractHebrew Translations of Palestinian Literature — From Total Denial to Partial Recognition — The present paper describes Hebrew translations of Palestinian literature written in the West Bank and Gazza Strip and the Palestinian diaspora and their gradual progress from total denial to partial recognition within the Hebrew cultural polysystem. The preface is followed by three sections: the attitude of Israeli Hebrew culture to translations from Palestinian literatures from the 1950s up to the present against the historical background of the Israeli-Palestinian conflict; the publication of translations of particular works by particular writers; Hebrew stage performances of adaptations of translated Palestinian literature.